Principles of Islamic Counseling - Syaiful Akhyar Lubis; Khadijah Khadijah; Sulaiman Syahdi (Universitas Islam Negeri (UIN) Sumatera Utara, 2019)
The results of thisresearch: 1) planning of the principle of monotheism in the application of Islamic counselingis still in development stage. 2) the effect of the principle of monotheism in the application ofIslamic counseling is very influential on the success of counseling guidance.3) theimplementation of the principle of monotheism in the application of Islamic counseling isquite good and the process of improvement in the application of Islamic counseling ongoing